2008
DOI: 10.1063/1.2839305
|View full text |Cite
|
Sign up to set email alerts
|

Carrier distribution in (0001)InGaN∕GaN multiple quantum well light-emitting diodes

Abstract: We study the carrier distribution in multi quantum well (multi-QW) InGaN light-emitting diodes. Conventional wisdom would assume that a large number of QWs lead to a smaller carrier density per QW, enabling efficient carrier recombination at high currents. We use angle-resolved far-field measurements to determine the location of spontaneous emission in a series of multi-QW samples. They reveal that, no matter how many QWs are grown, only the QW nearest the p layer emits light under electrical pumping, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
169
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(187 citation statements)
references
References 11 publications
13
169
2
3
Order By: Relevance
“…31 The "efficiency droop" is a common issue in nitride LEDs, 37,38 which is caused by a non-radiative carrier loss mechanism that has small effect at low J inject present in the active region, but becomes dominant at higher J inject. The main reason of the droop is still under debate as many different mechanisms have been proposed including Auger recombination, [39][40][41][42] "carrier overflow"/poor hole-injection efficiency, 35,43,44 and density-activated defects. 45,46 Generally, the much smaller droop of nonpolar and semipolar LEDs in comparison with polar LEDs has been attributed to the weaker polarization fields.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 The "efficiency droop" is a common issue in nitride LEDs, 37,38 which is caused by a non-radiative carrier loss mechanism that has small effect at low J inject present in the active region, but becomes dominant at higher J inject. The main reason of the droop is still under debate as many different mechanisms have been proposed including Auger recombination, [39][40][41][42] "carrier overflow"/poor hole-injection efficiency, 35,43,44 and density-activated defects. 45,46 Generally, the much smaller droop of nonpolar and semipolar LEDs in comparison with polar LEDs has been attributed to the weaker polarization fields.…”
Section: Resultsmentioning
confidence: 99%
“…56 Additionally, the rough surface morphology of the PSS-LED (Fig. 1) is another issue as it can cause nonuniform carrier distribution 21,44 and compositional fluctuations. 21 It has been previously found that polished PSS-GaN substrates can strongly enhance the luminescence uniformity of QWs and the performance of PSS-LEDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations where all quantum wells are identical, the relatively large effective mass of the holes, as compared to the effective mass of the electrons, tends to make hole transport the limiting factor in achieving a uniform carrier distribution. 8 The effect of barrier thickness on carrier distribution has also been studied in InGaAsP lasers where a large valence band offset is present. 9 Apart from their use in monitoring carrier distributions, multicolor LEDs are also useful as broad-spectrum LED sources.…”
mentioning
confidence: 99%
“…[1][2][3] In the past decade, multiple mechanisms have been proposed to explain the efficiency droop including Auger recombination induced by multi-particle interactions, [4][5][6][7][8] electron leakage due to poor hole injection and electron overflow, 9,10 carrier loss related to reduction or saturation of carrier localization, 11,12 and other processes including the density-activated defect recombination (DADR). 13,14 Some of these factors have been found to be tightly associated with the internal polarization field.…”
mentioning
confidence: 99%